The Essential Role of Hard Skills and Soft Skills in Shaping the Success and Future of University Students’ Education - Samosir, Sahat Maringan (Cendikia: Jurnal Pendidikan dan Pengajaran, 2025)
This article explores the significance of both skill sets for university students, emphasizing how a balance between hard skills and soft skills leads to improved academic performance and enhanced employability. The article examines the interdependence of these skills, focusing on how students can develop both to navigate the complexities of the modern workforce. The integration of these competencies is crucial for fostering not only technical expertise but also emotional and social intelligence, enabling students to contribute meaningfully to their communities and professional environments. The article concluded that both hard skills and soft skills play essential roles in shaping well-rounded individuals capable of achieving success in educational and professional settings. Hard skills refer to specific, technical abilities and knowledge directly related to a particular field, such as proficiency in technology, mathematics, or scientific expertise. On the other hand, soft skills, also known as emotional intelligence, encompass interpersonal abilities such as communication, problem-solving, leadership, empathy, and self-regulation—all critical for effective teamwork and personal growth.